2005
DOI: 10.1007/11562214_75
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Inducing a Part-of-Speech Tagger by Projecting from Multiple Source Languages Across Aligned Corpora

Abstract: Abstract. We implement a variant of the algorithm described by Yarowsky and Ngai in [21] to induce an HMM POS tagger for an arbitrary target language using only an existing POS tagger for a source language and an unannotated parallel corpus between the source and target languages. We extend this work by projecting from multiple source languages onto a single target language. We hypothesize that systematic transfer errors from differing source languages will cancel out, improving the quality of bootstrapped re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…In cross-lingual POS tagging, mostly annotation projection has been explored (Fossum and Abney, 2005;Das and Petrov, 2011), since all features in POS tagging models are typically lexical. However, using bilingual word representations was recently explored as an alternative to projectionbased approaches (Gouws and Søgaard, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In cross-lingual POS tagging, mostly annotation projection has been explored (Fossum and Abney, 2005;Das and Petrov, 2011), since all features in POS tagging models are typically lexical. However, using bilingual word representations was recently explored as an alternative to projectionbased approaches (Gouws and Søgaard, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fossum and Abney (2005) found that using two source languages project-sources gave better results than simply using more data from one language. also found advantages to using multiple language sources for projecting parsing constraints.…”
Section: Multilingual Projectionmentioning
confidence: 99%
“…It has also been used in cross-lingual POS tagging Fossum and Abney, 2005), NP-chunking ) and cross-lingual dependency parsing (Sukhareva and Chiarcos, 2014) before. and Fossum and Abney (2005) use word-aligned parallel translations of the Bible to project the predictions of POS taggers for several language pairs, including English, German, and Spanish to Czech and French. The resulting annotated target language corpora enable them to train POS taggers for these languages.…”
Section: Related Workmentioning
confidence: 99%
“…While it has been observed repeatedly that using multiple source languages improves performance Fossum and Abney, 2005;, most available techniques work best for closely related languages.…”
Section: Introductionmentioning
confidence: 99%